The Influence of Attitude, Health Consciousness, Environmental Concern, and Perceived Product Quality on Customer’ Purchase Intentions of Organic Products in Bangkok - บุรโกเสส ณัฐชยา; สุริยะ รักษิณา; เสนาไทย ฉันทรุจี; มะนาวหวาน สิริมา; ศรีติสาร ฐาปานีย์; หงษ์มา ทัศนา หงษ์มา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to examine the factors influencing customers’ purchase intention of organic products in Bangkok. The objectives of the study are: 1) To examine the level of importance of factors influencing customers’ purchase intention of organic products in Bangkok, 2) To investigate the level of importance of customers’ purchase intention of organic products in Bangkok, and 3) To study how factors such as attitude, health consciousness, environmental concern, and perceived product quality affect customers’ purchase intention of organic products in Bangkok. A questionnaire was used as the research instrument. The sample consisted of 400 individuals who have purchased organic products and reside in Bangkok, selected through non-probability sampling using the accidental sampling method. The statistical techniques employed include percentage, mean, standard deviation, and multiple regression analysis. The findings reveal that the overall level of importance of factors influencing customers’ purchase intention of organic products is high, with attitude being the most important factor. The overall level of importance of customers’ purchase intention of organic products is also high. Hypothesis testing showed that four factors significantly influenced customers’ purchase intention of organic products: 1) Attitude, 2) Health consciousness, 3) Environmental concern, and 4) Perceived product quality, with statistical significance at the 0.05 level.